RISIKO KURANG ENERGI KRONIS (KEK) PADA IBU HAMIL DI INDONESIA - ., Sandjaja (GIZI INDONESIA, 2009)
CHRONIC ENERGY DEFICIENCY AMONG PREGNANT WOMEN IN INDONESIAMaternal mid-upper arm circumference (MUAC) is a potential indicator of maternal nutritional status.It can serve as a predictor of low birth weight and other health related indicators. It is used inIndonesia to select woman of reproductive age and pregnant woman for nutrition intervention.However, there are few studies in Indonesia to examine risk factors associated with low MUAC. Theobjective of the study is to determine characteristics of areas, family, pregnant woman, and morbidityassociated with low MUAC (< 23.5 Cm), as a predictor of chronic energy deficiency. Data used for theanalysis is Riskesdas (Baseline Health Research) 2007. A total of 8187 pregnant women were used forthe analysis. The result showed that the prevalence of low MUAC in Indonesia was 21.6%, varied from11.8% in Riau to 32.4% in East Nusa Tenggara. The prevalence is higher in rural than that in urbanareas. The result also showed that high prevalence of low MUAC is associated with familycharacteristics (pregnant woman as dependent in the family, smaller and bigger household members,and poor quintiles of expenditure per capita). There was a negative association between theprevalence of low MUAC with age, education attainment, and height of mother. High prevalence oflow MUAC was found for single mother, jobless, farmer, unskilled labor. There was no cleardifference between low MUAC and morbidity or out-patient attendance in different type of healthfacilities. Keywords: pregnant woman, upper-arm circumference